Performance of Multi-Well Exploitation and Reinjection in a Small-Scale Shallow Geothermal Reservoir in Huailai County - Yuan, Wenzhen; Zhang, Dailei; Zhang, Yi; Gao, Jun; Liu, Tongzhe; Zhai, Haizhen; Jin, Guangrong; Wang, Guiling; Zhang, Baojian (Frontiers in Earth Science, 2021)
The sustainable development of shallow aquifer geothermal reservoir is strongly affected by the reinjection-production strategy. However, the reinjection-production strategy optimization of a small-scale exploitation unit with tens of meter well spacing is site-specific and not yet fulfilled. This study numerically investigates sustainable heat extraction based on various reinjection-production strategies, which were conducted in a single-phase aquitard–aquifer geothermal system in Huailai County, Hebei province, China. The response of water level and production temperature is mainly discussed. Numerical results show that production without reinjection induces the highest production temperature and also the water level drawdown. Although reinjection in a single doublet well system is conducive to the control of water level drawdown, the introduction of the thermal breakthrough problem causes the decrease in production temperature. The thermal breakthrough and sustainability of geothermal reservoirs highly depend on the well spacing between the production and reinjection wells, especially for the small-scale field. Therefore, a large well spacing is suggested. A multi-well system facilitates the control of water level drawdown while bringing intensive well interference and thermal breakthrough. Large spacing between the production and reinjection wells is also the basic principle for the design of the multi-well system. A decrease in openhole length leads to an increase in production temperature and output thermal power. An increase in production rate affect the thermal breakthrough highly and shortens the lifetime of the geothermal system. Furthermore, the extracted thermal energy is highly affected by the reduction in reinjection temperature. The results in this study can provide references to achieve sustainable geothermal exploitation in small-scale geothermal reservoirs.